Comparing the 1999 and 2007 Philippine NTA Estimates and Examining the Effects of a Definitional Change of Overseas Workers' Remittances - J.M. Ian S. Salas; Michael Ralph M. Abrigo; Rachel H. Racelis (Philippine Institute for Development Studies (PIDS), 2014)
This paper compares the estimates of the 1999 and 2007 Philippine National Transfer Accounts (NTA) and examines the implications of using two alternative treatments or definitions of overseas Filipino workers' (OFW) remittances in the NTA. To reflect official definitions in the Philippine System of National Accounts, the treatment of OFW remittances in the estimation is changed from being mainly interhousehold transfers in previous NTA estimates to being mainly labor income (earnings) in the revised NTA estimates. This results in a downward revision in lifecycle deficit estimates for 1999 and 2007, highlighting the sensitivity of estimates to definitional changes.
Keywords: 330; Philippines; National Transfer Accounts; economic lifecycle; intergenerational transfer; consumption age profile; lifecycle deficit; labor income age profile; overseas workers' remittances